T-cell Epitopes of Mycobacterium tuberculosis Antigen 85 Complex Potential for Generating Antibody: an Immunoinformatics Study - YOGY SIMANJUNTAK (Indonesian Society for microbiology, 2009)
The present study was conducted to predict T-cell epitopes of the antigen 85 complex capable of stimulating antibody generation by using immunoinformatics approaches. By applying computational biology software, the available data of the antigen 85 complex and related-epitopes would be turned into more constructive and useful scientific informations for the development of multiepitope-based anti-TB vaccine. The identification of T-cell epitopes capable of generating antibody was done by the 3DEX program, discotope analysis and PyMol program. Selected peptides having individual amino acids localized on the predicted antibody-binding sites were subjected to antigenic property analysis, including their hydrophilicity, flexibility and antigenic propensity. The 3DEX program identified 17 peptides having at least four individual amino acids located on the antigen surface. However, after homology analysis with preselected distance of 7 Å and taking into account the spatial neighborship, only seven peptides of antigen 85A, 85B and 85C (3, 3 and 1 peptide(s) respectively) had individual amino acids overlapping the predicted antibody-binding site. Peptides 17838, 21780, 21275 and 36131 had an average score of antigenic propensity above 1.0. In conclusion, there are seven peptides representing T-cell epitope of antigen 85 complex that could potentially be capable of generating an antibody response. The seven peptides, P17838, P21093, P36131, P21275, P21780, P21796 and P10839, are suitable candidates for further study in order to develop a subunit-based multiepitope anti-TB vaccine.